FINANCING ISSUES OF ENVIROMENT PROTECTION PROJECTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The aim of the report is to analyse the financial problems of the environmental protects in Latvia. The main tasks are the following: To become familiar with the formation o f various financial recourses on the environmental protects - the state budget investments, the local budgets sources, the grants and credits from International and other financial institutions. To analyse the structure of expenditures on environmental protection. The monographic method, the analyse statistic dates about environmental protection in Latvia in 1993-2000 are used the research. The main results o f the research are the following. The natural resources tax incomes are insufficient to solve the problems of the environmental protects. It is necessary to increase the base o f taxation. The incomes from ecology taxes must grow up on the summary state budget. It is necessary to increase the part o f natural resources tax to supliment local budgets, to solve local governments’ tasks o f environmental protection (especially garbage department) Till local financial resources are insufficient, it is necessary a supplement from state budgets to tie investments from various financial institutions.